Teaching Gender Through Films on Sportswomen: Contrary Messages - Chakravarty, Ankita (Voices of Teachers and Teacher Educators, 2020)
It is increasingly essential that teachers focus on media-based ways of teaching and learning. Hence, educators include films to provoke discussions and analyses of concepts. Scholars investigating women in films have shown the dominance of gendered constructions and representations. However, there are very few studies evaluating films on Indian sportswomen. This article assesses the utility of teaching gender and empowerment through two prominent films on sportswomen- Chak De! India and Bend it like Beckham. By engaging in critical content analysis, the article highlights that these films, ironically, predominantly identify sports with masculine achievements, wherein women’s successes become supporting narratives merely